PEMANFAATAN ROTAN OLEH MASYARAKAT DESA MERAGUN KECAMATAN NANGA TAMAN KABUPATEN SEKADAU - Riantono, Januarius; Hardiansyah, Gusti; Burhanuddin, . (Universitas Tanjungpura, 2018)
Rattan is one ofÂ non-timber forest product utilized by the community who lived near the frorest area. Meragun villagers in Nanga Taman District of Sekadau Regency use rattan to support their daily needs. The aims of this study were to identify rattan and to calculate the economic value of rattan utilization. The research was conducted in Meragun village, starting from April 2nd, to April 29 2018. The method used in this research was survey method with interview technique. Purposive sampling was used and 87 househald were selected. Several species of rattan are used by the Meragun community such as meiya (Korthalsia echinometra Becc), udang semut (Korthalsia scaphigera Mart), dahan (Korthalsia rigida Blume), taman (Calamus optimus Beccari), lilin (Calamus javensis Blume), sega (Calamus Caesius Blume), irit (Calamus trachycoleus Beccari), tohiti (Calamus inops Becc), manau riang (Calamus oxleyanus T et B), manau (Calamus manan Miq), uwi koroh (Daemonorops geniculata (Griff) Mart), penjalin manis (Daemonorops melanochaetes Bl) and jernang kecil (Daemonorops didymopphylla Bacc). The economic value of the utilization of rattan in the research area with average net income of Rp. 1.467.560 /year/family.Keywords: Meragun village, rattan utilization, rattan